2021
DOI: 10.3390/plants10030521
|View full text |Cite
|
Sign up to set email alerts
|

Hormetic Responses of Photosystem II in Tomato to Botrytis cinerea

Abstract: Botrytis cinerea, a fungal pathogen that causes gray mold, is damaging more than 200 plant species, and especially tomato. Photosystem II (PSII) responses in tomato (Solanum lycopersicum L.) leaves to Botrytis cinerea spore suspension application were evaluated by chlorophyll fluorescence imaging analysis. Hydrogen peroxide (H2O2) that was detected 30 min after Botrytis application with an increasing trend up to 240 min, is possibly convening tolerance against B. cinerea at short-time exposure, but when increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 89 publications
(163 reference statements)
0
60
0
Order By: Relevance
“…Other studies have reported a decreased NPQ upon pathogen attack, as early as 20 min after the attack, which was attributed to a reduced amount of PsbS, and it was proposed that NPQ regulation is a fundamental component of the plant’s defense program [ 71 ]. Defense response mechanisms can be triggered by NPQ so that light energy allocation is adjusted in order to have an enhanced PSII functionality [ 31 ]. The decreased NPQ immediately after feeding was probably caused by a reduction in the protein levels of the PSII subunit protein PsbS [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have reported a decreased NPQ upon pathogen attack, as early as 20 min after the attack, which was attributed to a reduced amount of PsbS, and it was proposed that NPQ regulation is a fundamental component of the plant’s defense program [ 71 ]. Defense response mechanisms can be triggered by NPQ so that light energy allocation is adjusted in order to have an enhanced PSII functionality [ 31 ]. The decreased NPQ immediately after feeding was probably caused by a reduction in the protein levels of the PSII subunit protein PsbS [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, photosynthetic functioning is not homogeneous at the leaf surface, which makes standard chlorophyll fluorescence analysis non-representative of the photosynthetic status of the whole leaf [ 27 , 28 , 29 ]. The development of chlorophyll fluorescence imaging has overcome those challenges by allowing us to study the spatial heterogeneity of leaves [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide generation was noticed only at the feeding zone and did not spread out to the rest of the leaf ( Figure 6 ). It has been frequently observed to diffuse through the leaf veins acting as a molecule that triggers a long-distance stress defense response [ 24 , 28 , 36 , 38 , 41 , 52 , 84 ] or induces programmed cell death in plants [ 41 , 42 ]. In contrast to the local production of ROS, the increased NPQ at the whole leaf level may be suggested as a major component of the systemic acquired resistance [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, photosynthetic function is not homogeneous at the leaf surface; as a result, standard chlorophyll fluorescence analysis is not characteristic of the photosynthetic status of the whole leaf [ 45 , 46 , 47 , 48 , 49 , 50 ]. The development of the method of chlorophyll fluorescence imaging overcomes this problem by being capable of identifying spatial heterogeneity of leaf photosynthetic performance at the whole leaf surface and by monitoring early changes in a plant’s physiological status upon early biotic stress cases, before visual symptoms appear [ 51 , 52 , 53 ]. The chlorophyll fluorescence imaging method is appropriate for visualizing the heterogeneity in plant responses to biotic stresses at an early stage against a background of unaffected plant tissue [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, ROS produced in chloroplasts are not only creating oxidative stress but also confer significant biological functions, such as redox signaling in the regulation of leaf development and translating information from the environment [ 69 , 70 , 74 , 80 , 81 , 82 ]. NPQ has also been suggested to be involved in the mechanism of plant acclimation to biotic or abiotic stress and to be a major component of the systemic acquired resistance [ 66 , 70 , 83 , 84 , 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%